Principal's Leadership Style and Influence Workload Against Teacher Performance - Saleh, Sirajuddin; Arhas, Sitti Hardianti; ., Isgunandar; ., Nasaruddin; ., Sulmiah (KnE Social Sciences, 2024)
This study attempts to examine teacher performance as influenced by the principal’s leadership and workload. This study seeks to reveal the effect of the principal’s leadership style and workload on teacher performance. While the specific target to be achieved in this research is to serve as information material in the development of science, especially in the field of education and teacher training. The approach used is quantitative with the type of associative research. This study focuses on three variables, namely the principal’s leadership style (variable X1), teacher workload (X2), and teacher performance (Y). All state high school teachers in Makassar City were used as the study population. As many as 163 of the total population were used as research samples taken using proportional random sampling technique. Data was collected using questionnaires, observation, and documentation techniques. Data were obtained through a questionnaire instrument and analyzed using inferential statistics. The results of the data analysis show: 1) the principal’s leadership style has a positive and significant effect on teacher performance; 2) workload has a positive and significant effect on teacher performance; 3) the principal’s leadership style and teacher’s workload together have a positive and significant influence on teacher performance. Keywords: leadership, workload, teacher performance